A Systemic-Functional Model for Foreign Language Instruction in Tourism Service Contexts - Susianti, Hartanti Woro; Suandi, I Nengah; Putrayasa, Ida Bagus (Universitas Negeri Makassar, 2025)
Abstract. Foreign language learning in vocational tourism institutions, such as the Bali Tourism Polytechnic, still faces challenges in developing students’ communicative competence that is both contextual and functional. This study aims to describe the fundamental principles of Systemic Functional Linguistics (SFL) and to design an SFL-based German language learning model tailored to the professional communication needs of the tourism sector. Employing a descriptive qualitative approach, the research was conducted through three main stages: a literature review, content analysis of authentic German tourism texts (e.g., hotel reservation dialogues, brochures, service emails, and spoken interactions), and the design of a learning model. The research instrument consisted of an SFL-based analytical grid covering ideational, interpersonal, and textual metafunctions to identify how language is used in professional tourism contexts. The findings demonstrate that integrating SFL into learning enables students to produce oral and written texts that are more contextual, communicative, and professionally appropriate, such as handling hotel reservations, providing travel information, and responding to customer complaints. The novelty of this study lies in applying SFL to German language learning within vocational tourism education, a field that has received little attention compared to English. Its broader implication is that an SFL-based learning model can serve as a framework for developing foreign language curricula in vocational education that are more practical, adaptive, and aligned with the demands of the global tourism industry. Keywords: German, Systemic-Functional Linguistics, vocational learning, tourism, text genres